The social role of love in the teachings of Erich Fromm and Pitirim Sorokin - Nedeljković, Zoran D.; Semenov, Andrej (Sociološki pregled, 2025)
Drawing on the relevant literature, the authors of this paper explore the interpretations of the concept of love in the theories of Erich Fromm and Pitirim Sorokin. Using a comparative historical method and a hermeneutic approach, they analyze the similarities and differences in how the concept of love is understood in their respective texts. Both thinkers share a critical attitude towards contemporary society: while Fromm criticizes its deep alienation, Sorokin focuses on the non-solidaristic nature of the consumer capitalist system. Fromm, as a social psychologist and representative of critical theory, understands love as a capacity that must be cultivated within the context of interpersonal relationships. In contrast, Sorokin, a sociologist of culture, rejects the views of Marxist and Freudian followers and develops the idea of love as a transcendent force with the potential for the moral and social renewal of humanity, consistent with his cyclical theory of social development.
Keywords: love; altruism; alienation; solidarity; Sorokin; Fromm